Techno-Economic Analysis of Hydraulic Fracturing As A Solution for Developing Low-Resistivity and Low-Quality Zone on Offshore “RI” Field - Steven Chandra; Ilma Mauldhya Herwandi (Universitas Islam Riau (UIR) Press, 2021)
Hydrocarbon production in Indonesia is continuously decreasing on a yearly basis, which is in contrast with its increasing level of consumption. Low-quality and low-resistivity reservoir zones are deemed to possess a lot of hydrocarbon potentials, however, little priority has been placed on their development due to their small level of production. The